2013
DOI: 10.1155/2013/175428
|View full text |Cite
|
Sign up to set email alerts
|

Immunohistochemical Localization ofAT1a,AT1b<

Abstract: Angiotensin II increases blood pressure and stimulates thirst and sodium appetite in the brain. It also stimulates secretion of aldosterone from the adrenal zona glomerulosa and epinephrine from the adrenal medulla. The rat has 3 subtypes of angiotensin II receptors: AT1a, AT1b, and AT2. mRNAs for all three subtypes occur in the adrenal and brain. To immunohistochemically differentiate these receptor subtypes, rabbits were immunized with C-terminal fragments of these subtypes to generate receptor subtype-speci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
33
0

Year Published

2014
2014
2016
2016

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(37 citation statements)
references
References 180 publications
(219 reference statements)
4
33
0
Order By: Relevance
“…However, we cannot explain why the 44-kDa band detected by Sc1473 in murine heart disappeared in knockout animals when studied by Bundgaard et al (2010) but not by us. Of note, in line with our findings, it has recently been discussed whether the lack of disappearance of staining with antibodies directed against the C-terminus of the AT 1a angiotensin II receptor in corresponding knockout mice may represent false negative data because that disruption also did not eliminate the C-terminus (Premer et al 2013). Thus, knockout approaches causing functional inactivation of a receptor but not eliminating expression of its C-terminus may be an inappropriate approach for the testing of antibodies raised against this part of the receptor.…”
Section: Discussionsupporting
confidence: 88%
“…However, we cannot explain why the 44-kDa band detected by Sc1473 in murine heart disappeared in knockout animals when studied by Bundgaard et al (2010) but not by us. Of note, in line with our findings, it has recently been discussed whether the lack of disappearance of staining with antibodies directed against the C-terminus of the AT 1a angiotensin II receptor in corresponding knockout mice may represent false negative data because that disruption also did not eliminate the C-terminus (Premer et al 2013). Thus, knockout approaches causing functional inactivation of a receptor but not eliminating expression of its C-terminus may be an inappropriate approach for the testing of antibodies raised against this part of the receptor.…”
Section: Discussionsupporting
confidence: 88%
“…In addition to AT 1a Rs, ANG II can also activate brain AT 1b Rs. However, whether AT 1b Rs are present in the PVN is controversial, with studies supporting (14,58) or arguing against (30,39) its presence within the PVN. Since both AT 1 R subtypes share similar intracellular signaling pathways, we cannot rule out at present a possible role for AT 1b Rs in ANG II-mediated ROS production in the PVN.…”
Section: Tlr4 In Microglia Is Involved In Ang Ii-mediated Ros Within mentioning
confidence: 99%
“…Apart from their role in cardiovascular regulation, RAS components within the central nervous system have other functions mediated by AT 1 and/or AT 2 receptors (Paul et al, 2006;Premer et al, 2013;Wright and Harding, 2011). In particular, previous studies have demonstrated that several neuromodulators, including angiotensin II acting on AT 1 receptors, are involved in cardiovascular regulation within the NTS (Arnold et al, 2010;Cheng et al, 2010Cheng et al, , 2012Kasparov et al, 1998;Mosqueda-Garcia et al, 1990).…”
Section: Introductionmentioning
confidence: 99%
“…In particular, previous studies have demonstrated that several neuromodulators, including angiotensin II acting on AT 1 receptors, are involved in cardiovascular regulation within the NTS (Arnold et al, 2010;Cheng et al, 2010Cheng et al, , 2012Kasparov et al, 1998;Mosqueda-Garcia et al, 1990). Accordingly, high levels of ACE (Rogerson et al, 1995) and high densities of AT 1 receptors have been found at the level of the NTS in the rabbit (Aldred et al, 1993) as well as in many other mammals including humans (Paul et al, 2006;Premer et al, 2013;Wright and Harding, 2011). …”
Section: Introductionmentioning
confidence: 99%